Risk of developing severe sepsis after acute kidney injury: a population-based cohort study - Lai, Tai-Shuan (BioMed Central, 2013)
INTRODUCTION: Sepsis has been a factor of acute kidney injury (AKI); however, little is known about dialysis-requiring AKI and the risk of severe sepsis after survival to discharge. METHODS: We conducted a population-based cohort study based on the Taiwan National Health Insurance Research Database from 1999 to 2009. We identified patients with AKI requiring dialysis during hospitalization and survived for at least 90 days after discharge, and matched them with those without AKI according to age, sex, and concurrent diabetes. The primary outcome was severe sepsis, defined as sepsis with a diagnosis of acute organ dysfunction. Individuals who recovered enough to survive without acute dialysis were further analyzed. RESULTS: We identified 2983 individuals (mean age, 62 years; median follow-up, 3.96 years) with dialysis-requiring AKI and 11,932 matched controls. The incidence rate of severe sepsis was 6.84 and 2.32 per 100 person-years among individuals with dialysis-requiring AKI and without AKI in the index hospitalization, respectively. Dialysis-requiring AKI patients had a higher risk of developing de novo severe sepsis than the non-AKI group. In subgroup analysis, even individuals with recovery from dialysis-requiring AKI were at high risk of developing severe sepsis. CONCLUSIONS: AKI is an independent risk factor for severe sepsis. Even patients who recovered from AKI had a high risk of long-term severe sepsis.